PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT TOMA KABUPATEN NIAS SELATAN - Duha, Florentina Meldawati (LPPM Universitas Nias Raya, 2022)
The problems of this research are the lack of trust given by the leadership to their subordinates, the presence of leadership that does not pay attention to the complaints and needs of employees, the lack of awards and recognition to employees who excel and employees have low work achievements with delays in completing the tasks given. The purpose of this study was to determine the effect of leadership and work motivation on employee performance at the Toma sub-district office, South Nias district. This type of research is a quantitative research. The subjects in this study were all 32 employees of the Toma Sub-district Office of South Nias Regency. The results showed that Leadership and Work Motivation had a significant influence on employee performance at the Toma Sub-district Office, South Nias Regency. Suggestions put forward by researchers are 1) to improve employee performance at the Toma Sub-District Office, it is necessary to have trust from the leadership to their subordinates. 2) it is expected that the leadership at the Toma Sub-district Office will pay attention to employee complaints and needs. 3) it is expected that all employees of the Toma Sub-district Office to further improve their performance through high work motivation and good motivation from the leadership element. 4) it is hoped that the employees at the Toma Sub-district Office will be able to complete the work effectively.